(untitled) (International Journal of Nursing Education, 2022)
Background: Interprofessional collaboration is considered important and often carried out in an inpatient setting. Therefore, the common perception amongst professional care providers is needed to ensure the implementation of the Interprofessional collaboration in hospitals. However, there are still obstacles that cause limitations in the implementation of Interprofessional collaboration in practices. Objectives: The purpose of the study was to explore professional experience of care givers in the implementation of interprofessional collaboration at one of general public hospitals in the capital of Aceh Province, Indonesia. Methods: This qualitative research used phenomenological study design. Data were collected using in-depth interviews with five participants in one inpatient room of the selected general public hospital. The Collaizi method was used to analyze the data. Results: The study identified four themes: (1) The implementation of Interprofessional collaboration was perceived as integrated care; (2) Application of values, ethics and professionalism in Interprofessional collaboration are important; (3) Collaboration as a responsibility between caregiver profesionals, and; (4) Lack of communication and teamwork can be as barriers to Interprofessional collaboration implementation. Based on the findings, hospital managers are recommended to consider the existance of obstacles in the implementation of interprofessional colaboration and to develop standard operating procedures on interprofessional colaboration.